The Influence of Liquidity Ratio and Solvency Ratio on Profitability Ratio of PT Apexindo Pratama Duta Tbk - Fabiola Latifah Basjah; Delila Pandora Harlacxienty; Kurnia Illa Allodya Dinara; Maria Yovita R Pandin (International Journal of Economics, Management and Accounting, 2024)
This investigation was conducted to examine the impact of liquidity ratios and solvency ratios on the profitability ratio of PT Apexindo Pratama Duta Tbk. Using quantitative methods, this investigation seeks to ascertain the company's capacity to manage its liquidity and solvency aspects, it is anticipated to have a favorable effect on profitability. The results of the analysis show that although the company shows good liquidity, the high level of leverage and difficulty in generating average profits indicates challenges in managing profitability. This research recommends that companies focus more on debt management and optimizing funding structures to increase their profitability. More investigation is required to understand other elements that may influence the financial performance of these companies, as well as to identify strategic steps to increase the company's profitability in the future.